Exploring the Role of Cymbopogon citratus Essential Oil as a Natural Inhibitor of Serine Palmitoyltransferase in Leishmania donovani - Abdullah, Mahmmoud Shakir; Alqaisi, Amjed Qays Ibrahim (Iraqi Journal of Science, 2026)
The Leishmania parasite is divided into two main divisions: the old-world Leishmania species and the new-world Leishmania species. The antileishmanial medications currently in use have a number of side effects, for instance, their toxicity to humans, liver issues, long-term treatment, and extreme cost. Cymbopogon citratus is a herbal medicine used as an anti-inflammatory, antibacterial, antifungal, antiprotozoal, and gastrointestinal disturbances remedy. Sphingolipids (SLs) in many eukaryotes, one of the important cell membrane components, and their metabolites interfere with the control of many vital functions in the cell, such as cell growth, apoptosis, and differentiation. In this study, the essential oil of C. citratus with concentration of 500 µg / ml is selected to test its activity against serine palmitoyltransferase (SPT) enzyme gene expression at different periods (24, 48, and 72 hours post-treatment). The results of the gene expression tested by the RT-qPCR technique showed downregulation of the SPT enzyme gene in treated parasites compared with untreated parasites (control). This study represents the first investigation to study the effect of the crude essential oil extracted from C. citratus on the SPT enzyme in L.donovani promastigote stage in Iraq.